CORELESS INDUCTION FURNACE. CONSTRUCTIVE DIFFERENCES, OPERATION - A. N. Saharevich (Литьë и металлургия)
The main tendencies of development of induction crucible furnaces are considered. constructive differences of crucible furnaces in comparison with fuel furnaces are given. The area of their application is specified.